Analyzing the Application and Ecological Value of Green Roofs in Urban Environmental Art Design - Zhang Jingyi (MATEC Web of Conferences, 2025)
Green roofs, integrated into urban environmental art design in a natural manner, not only decorate the city skyline, but also have ecological functions such as adsorption of pollutants and mitigation of the heat island effect, becoming a green engine for sustainable urban development. At the same time, the rapid development of high-tech rooftop agriculture is expected to bring considerable ecological and economic benefits. Despite the cost and technical challenges, green roofs have a promising future, and new technologies and policy incentives will promote their widespread use as an important strategy for sustainable urban transformation. This paper analyzes the ecological function, aesthetic effect, and positive impacts of green roofs on the urban environment, fully demonstrating the importance and feasibility of green roofs in urban environmental art design, and providing a theoretical basis and practical reference for sustainable urban development.